Políticas afirmativas, educação e escolas públicas: uma análise sobre o sistema de cotas - Caso UFPA - SILVA, Carlos Fernando Cruz da (Universidade Federal do Pará, 2018)
The present research discusses the affirmative actions instituted at the Federal University of Pará, in the modality quotas for undergraduate courses, destined to students who attended high school in institutions of the educational public network. The investigation is based on different studies on inequality and social exclusion of authors such as: Boaventura de Souza Santos, Amartya Sen, Ingrid Robeyns and Zélia Amador de Deus. It is also supported by studies on education and educational systems developed by Jan Masschelein, Marteen Simons, Dermeval Saviani, Pierre Bourdieu and Jean-Claude Passeron, apart from the critical thinking of Michel Foucault. Social inequality, social exclusion, substantive liberties, device and reproduction were frequently used as analytical categories during the development of the research. During the study, questions about the dynamics of transition from high school to higher education through affirmative action policies are inserted, focusing on the situation of public schools coordinated by institutions of the National Armed Forces. The hypothesis is that school, administrative and non-administrative practices developed in this space, in part, have repercussions on the quota policy instituted at the Federal University of Pará. From the proposed problem, it is intended to open space for academic discussion about the transition process to higher education in the contemporary Brazilian educational system, which can be directed to other institutions and other specific contexts.